Pengaruh pemberian asi eksklusif terhadap status gizi dan perkembangan bayi di puskesmas gamping II - Wahyu Widayati; Detty Siti Nurdiati; Anjarwati Anjarwati (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2016)
Abstract: This study aims to find out the correlation of exclusive breast- feeding and the nutrional status and development of infant aged 6-12 months old. This is an observational analytical research. The data are analyzed using bivariate analysis of ChiSquare and multivariariate logistic regression. Based on bivariate analysis, there is a significant evidence regarding the correlation between exclusive breastfeeeding and infant nutrional status, as the value is OR 21.317;95% CI 2.761-164.565. The bivariate analysis in exclusive breastfeeding and infant development shows that there is a significant evidence in exclusive breastfeeding and infant development as the value is OR 6.000; 95% CI 2.548 – 14.130.